Environmental footprint of the integrated France–Italy beef production system assessed through a multi-indicator approach. (July 2017) - Berton, Marco; Agabriel, Jacques; Gallo, Luigi; Lherm, Michel; Ramanzin, Maurizio; Sturaro, Enrico
Abstract: This study aims to evaluate the environmental footprint of the integrated France–Italy beef production system (extensive grassland-based suckler cow-calf farms in France with intensive cereal-based fattening farms in northeastern Italy) using a multi-indicator approach, which combines environmental impact categories computed with a cradle-to-farm gate Life Cycle Assessment, and food-related indicators based on the conversion of gross energy and protein of feedstuffs into raw boneless beef. The system boundaries were set from the calves' birth to their sale to the slaughterhouse, including the herd management, on- and off-farm feed production and materials used on the farms. One kilogram of body weight (BW) sold was used as the functional unit. The study involved 73 Charolais batches (i.e., a group of animals homogenous for age, finishing period and fattening farm), kept at 14 Italian farms. Data from 40 farms originating from the Charolais Network database (INRA) were used to characterize the French farm types, which were matched to the fattening batches according to the results of a cluster analysis. The impact categories assessed were as follows (mean ± SD per kg BW): global warming potential (GWP, 13.0 ± 0.7 kg CO2 -eq, reduced to 9.9 ± 0.7 kg CO2 -eq when considering the carbon sequestration due to French suckler cow-calf system permanent grassland), acidification potential (AP, 193 ± 13 g SO2 -eq), eutrophication potential (EP, 57 ± 4 g PO4 -eq), cumulative energy demand (CED, 36 ± 5 MJ), and land occupation (LO, 18.7 ± 0.8 m 2 /year). The on-farm impacts outweighed those of the off-farm activities, except in the case of CED. On average, 41 MJ and 16.7 kg of dietary feed gross energy and protein were required to provide 1 MJ or 1 kg of protein of raw boneless beef, respectively, but nearly 85% and 80%, respectively, were derived from feedstuffs not suitable for human consumption. Emission-related (GWP, AP, EP) and resource utilization categories (CED, LO) were positively correlated. Food-related indicators showed positive correlations with emission-related indicators when the overall feedstuffs of the diet were considered but negative correlations when only the potentially human-edible portions of the beef diets were considered. In conclusion, the integration of the pasture-based France suckler cow-calf system with the cereal-based Italian fattening farms allows for the exploitation of the resources available, increasing the share of non-human-edible feedstuffs while maintaining good livestock productive efficiency. Combining indicators of impact categories with indicators of feed net supply may improve the assessment of the environmental footprint of livestock systems. Highlights: The environmental footprint of the integrated France–Italy beef system was assessed. The multi-indicator approach considered environmental impact and food security. Pollutant emissions and human-edible feed conversion ratio were negatively correlated. Land occupation due to cropland was comparable with that of monogastric systems. Use of multi-indicator approach improved the environmental footprint assessment.